2012
DOI: 10.1016/j.pain.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of remifentanil-induced postinfusion hyperalgesia by the β-blocker propranolol in humans

Abstract: Acute and chronic exposure to opioids has been associated with hyperalgesia in both animals and humans. A genetic analysis of opioid-induced hyperalgesia in mice linked the β(2)-adrenergic receptor to mechanical sensitization after opioid exposure. In humans, expansion of the area of mechanical hyperalgesia surrounding an experimentally induced lesion after the cessation of remifentanil infusion is a commonly used model of opioid hyperalgesia (remifentanil-induced postinfusion hyperalgesia, RPH). The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 63 publications
0
32
0
Order By: Relevance
“…Ackerman [40] described a similar outcome in 28 % of a sample of 197 patients with chronic pain receiving opioids. While some studies suggest that OIH develops after chronic opioid use [41][42][43], both rodent [44,45] and human studies [46][47][48][49] have documented OIH within hours of acute opioid administration. Studies using shorter-acting opioids such as remifentanil, sufentanil, fentanyl, and morphine provide the most suspicion of OIH [49][50][51][52][53][54][55][56]; however, there is documentation of this phenomenon in patients receiving long-acting opioids (e.g., methadone or buprenorphine) as well [23,43,[57][58][59][60].…”
Section: Prevalence Of Oih In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Ackerman [40] described a similar outcome in 28 % of a sample of 197 patients with chronic pain receiving opioids. While some studies suggest that OIH develops after chronic opioid use [41][42][43], both rodent [44,45] and human studies [46][47][48][49] have documented OIH within hours of acute opioid administration. Studies using shorter-acting opioids such as remifentanil, sufentanil, fentanyl, and morphine provide the most suspicion of OIH [49][50][51][52][53][54][55][56]; however, there is documentation of this phenomenon in patients receiving long-acting opioids (e.g., methadone or buprenorphine) as well [23,43,[57][58][59][60].…”
Section: Prevalence Of Oih In Humansmentioning
confidence: 99%
“…Following the results of a genetic study linking the b-adrenergic receptor to OIH [210], speculation arose regarding the clinical therapeutic effect of propranolol in treating OIH. Accordingly, Chu et al [47] conducted a clinical trial in which propranolol effectively eliminated secondary hyperalgesia in healthy volunteers receiving remifentanil infusion and undergoing experimental pain testing ( Table 3). As such, propranolol may prove useful in precluding OIH; however, further studies are needed.…”
Section: Propranololmentioning
confidence: 99%
“…It provides adequate and controllable analgesia, and has a rapid onset of action without accumulation effects after intravenous infusion (Bürkle et al, 1996). However, experimental and clinical studies implied that remifentanil might induce hyperalgesia after surgery, or worsen postoperative pains (Joly et al, 2005;Troster et al, 2006;Singler et al, 2007;Chu et al, 2012). Guignard et al (2000) found that hyperalgesia occurred in patients with colon surgery after infusion of remifentanil at 6 μg/kg and 18 μg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…We expect genetic approaches in mice to also be informative, since there are very large differences in the response of inbred strains to opiates, including the development of opioid analgesia, tolerance, dependence and hyperalgesia [814]. In fact, HBCGM, which used SNP databases generated from limited sequence information, has identified several involved genes including those coding for β2-adrenergic and 5-HT3 receptors that affect opiate responses, and these findings were translated to humans [8, 15]. …”
Section: Introductionmentioning
confidence: 99%